Elucidating Atropisomerism in Nonplanar Porphyrins with Tunable Supramolecular Complexes - Senge, Mathias (My University, 2021)
Atropisomerism is a fundamental feature of substituted biaryls resulting from rotation around the biaryl axis. Different stereoisomers are formed due to restricted rotation about the single bond, a situation often found in substituted porphyrins. Previously NMR determination of porphyrin atropisomers proved difficult, if not almost impossible to accomplish, due to low resolution or unresolvable resonance signals that predominantly overlapped. Here, we shed some light on this fundamental issue found in porphyrinoid stereochemistry. Using benzenesulfonic acid (BSA) for host‐guest interactions and performing 1D, 2D NMR spectroscopic analyses, we were able to characterize all four rotamers of the nonplanar 5,10,15,20‐tetrakis(2‐aminophenyl)‐2,3,7,8,12,13,17,18‐octaethylporphyirin as restricted H‐bonding complexes. Additionally, X‐ray structural analysis was used to investigate aspects of the weak host–guest interactions. A detailed assignment of the chemical signals suggests charge‐assisted complexation as a key to unravel the atropisomeric enigma. From a method development perspective, symmetry operations unique to porphyrin atropisomers offer an essential handle to accurately identify the rotamers using NMR techniques only.
Keywords: Atropisomers; Crystallography; NMR; Porphyrinoids; Supramolecular chemistry